An end to global warming - Williams, L. O.; ScienceDirect eBooks (Amsterdam ; Boston : Pergamon, 2002)
The 6+ billion inhabitants of earth aspire to higher standards of living. This takes energy. If fossil fuels continue to be the key source of energy their waste product, carbon dioxide, will produce disagreeable changes in the climate. Depletion of fossil fuels will cause the cost of energy and fuel based chemicals to spiral. Climate change and high fuel prices will thwart these aspirations and will increase the probability of lethal international conflicts over energy supplies. We must stop using fossil fuels. Optimistically, we could switch from fossil fuels to renewable energy sources (solar, wind, etc.). Regrettably these sources are difficult to harvest and unreliable. They cannot, alone, serve as a base load energy supply for humanity. Fission nuclear power yields extremely hazardous waste for which no fully agreeable disposal method has been developed. Laurence Williams applied aerospace systems analysis techniques to seek a new energy system. An End to Global Warming presents his results. He shows why we must stop using fossil fuels and evaluates a host of alternatives to arrive at a robust energy system that will modernize world energy production and protect the environment. A by-product of this system will ameliorate problems associated with supplying potable water and in processing waste. The nations that develop the system described in An End to Global Warming will be gifted with huge financial reward and the pride in knowing that they have preserved the earth for all mankind.
Fossil fuels. Alternative energy sources. The energy source-nuclear fusion reactors. A chemical fuel is required. Hydrogen, the optimum fuel. The fusion-hydrogen energy system. Hydrogen as a transportation fuel. Oxygen-the beneficial by-product. Implementation. Synopsis. Index.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Hydrogen as fuel; Power resources; Hydrogen as fuel; Power resources; Electronic books